ANALISIS PERKEMBANGAN REKSADANA SYARIAH DAN REKSADANA KONVENSIONAL - Khoirika Latifa Bintasima (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2020)
Seeing the booming mutual fund phenomenon, this study aims to determine, describe, and analyze the development of sharia mutual funds and conventional mutual funds. The data collection as analytical material was taken from 2015 to 2019. The method used in this research is descriptive with a comparative study, which comparing the Net Asset Value (NAV) from the statistics of Islamic mutual funds and conventional mutual funds. The results of this study show that the development of sharia mutual funds and conventional mutual funds has increased every year, it's just that there is a far comparison of achievements between the two, conventional mutual funds have higher achievements than sharia mutual funds. Keywords: Sharia Mutual Funds, Conventional Mutual Funds, Total Mutual Funds, and Net Asset Value